Integrating the Whoop It Up Strategy with the AIR (Auditory, Intellectually, Repetition) Learning Model in Arabic Language Learning - Taufik, Taufik; Febriani, Nailin Nabilah; Dimyathi, Muhammad Afifudin; Abdullah, Rafidah Binti Hj (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This research comprehensively describes implementing the "Whoop it Up" strategy in Arabic language learning integrated with the AIR model (Auditory, Intellectually, Repetition) Learning Model in Arabic Language Learning at MTs Bilingual NU Pucang. The research employs a qualitative descriptive approach through detailed observation and analysis, enhancing active student engagement, peer interaction, and reflection on the learning material. Within the AIR model, Arabic language learning goes beyond a passive process, involving students actively in language use, encouraging peer interaction, and fostering reflection on their understanding of the material. The combination of these two approaches offers diverse advantages. It can create a more engaging and interactive learning experience. At the same time, the AIR model provides additional structure and resources to support student understanding to create a dynamic learning environment, motivating students to participate actively and providing a holistic learning experience in comprehending and using the Arabic language. This research contributes valuable insights to develop innovative and effective teaching methods in the context of Arabic language learning.